Social Order in Middletown, 1932-1975 - Hewitt, John ([Verlag nicht ermittelbar], 1985)
The purpose of this study was to examine crime over a period of 43 years in Muncie, Indiana, which has commonly been referred to as "Middletown" in social science studies. The unit of analysis is the criminal act charged. All charges were counted and appropriately categorized. The following rules were observed for cases involving multiple charges or multiple counts of single charges. First, each charge was counted separately when multiple charges were filed. Second, when a defendant was charged with multiple counts of a single charge, each count was considered to be a separate act and so recorded. Data are provided on year of criminal act charge, first, second, and third offenses charged, legal representation by public defender, amount of bail, nature of plea, and place and length of prison terms (Part 2). Other items specify city population, unemployment rate, and total jobs in nonfarm industries, as well as the number of police, reported charges and convictions for murders, rapes, assaults, and robberies, and the percentage of felons convicted for murder, rape, assault, and robbery that were incarcerated (Part 5). Additional variables provide the socioeconomic index, as well as other information on criminal cases such as initial charges, prior records and number of prior felony convictions, marital history, and work history of offenders, and prosecutors' recommended sentencings, actual number of months in jail, and probation and jail terms (Part 6). Demographic items specify age, sex, and race (Parts 2 and 6), as well as education and occupation (Part 6) of the alleged defendant.